Associação da alternância dos turnos de trabalho com o horário de comer e com as percepções subjetivas relacionadas à ingestão alimentar em trabalhadores rodiziantes. - Furlan, Luisa Pereira Marot (2022)
Introduction: Previous studies have highlighted the irregularity in the eating patterns of shift workers, mainly regard mealtimes and frequency. However, little is known about the impact of shift rotation between day, evening and night work hours and free days, on total energy intake and 24-hour energy and macronutrient distribution and subjective perceptions related to the meal. Objective: To evaluate the effect of a clockwise rotating a shift schedule on: 1) total energy intake and distribution of energy and macronutrients by time range over 24 hours; 2) and on the variation of subjective perceptions of hunger before, meal enjoyment, post-meal satiety and appetite by food groups. Methods: Thirty male shift workers from a mining company of the Midwest of Brazil were evaluated over 240 consecutive hours (10 days of the shift schedule: 2 days in the morning shift (Day 1 and Day 2 or Morning 1 and Morning 2- 08:00 - 16:00); 2 days in the evening shift (Day 3 and Day 4 or Afternoon 1 and Afternoon 2)- 16:00 - 00:00); 24 hours free (Day 5 or 24h Free - 00:00 - 00:00); 2 days in the night shift (Day 6 and Day 7 or Night 1 and Night 2 - 00 :00 - 08:00) and 3 days off (D8, D9 and D10 or Free 1, Free 2 and Free 3). Food intake was evaluated by 24h recall (24hR) and the subjective perceptions related to the meal (hunger, meal enjoyment, satiety and appetite for food groups) by a visual analogue scale. Linear mixed models were used to analyze the effect of shift rotation on variation of meal times, energy and macronutrients intake; effect of the interaction between shift and time ranges (00:00-03:59, 04:00-07:59, 08:00-11:59, 12:00-15:59, 16:00-19:59, 20:00-23:59); on the variation in the rates of hunger before meal, meal enjoyment, satiety after meal, appetite for food groups and energy intake in the main meal of the shift, as well as the interaction of meals with the rotation of shifts on the food perception variables. Results: Shift rotation had no effect on energy intake in 24h (p = 0.065). The interaction between shift day and time range showed that on night shift days (Day 6 and Day 7) there was a higher energy intake (D6: 441.5 ± 48.4 kcal, D7: 345.5 ± 48.4 kcal ), fats (D6: 17.6 ± 2.0 %, D7: 15.1 ± 2.0 %), carbohydrate (D6: 17.0 ± 1.7 %, D7: 14.0 ± 1.7 % ) and protein (D6: 16.4 ± 1.8 D7: 15.5 ± 1.8) between 00:00 - 03:59, compared to the other shift days (p<0.05). Regarding the subjective perceptions related to meals, an isolated effect of the shift showed higher hunger rates on the second day of the night shift (N2: 6.4 ± 0.4) compared to the morning shifts (M1: 4.7 ± 0. 4, p < 0.001 and M2: 5.4 ± 0.4, p = 0.005) and second day of the afternoon shift (A2: 5.6 ± 0.3, p = 0.31). The interaction between shift and meal showed that the last day of shift (N2) presented 9 higher values of hunger compared to Morning 1, Morning 2 and Afternoon 2, at breakfast (N2: 6.4 ± 0.4; M1: 5.2 ± 0.4 0.4, p = 0.14; M2: 5.3 ± 0.4, p = 0.029; A2: 5.2 ± 0.4, p = 0.022) and morning shifts in the after-dinner meal (N2: 5.4 ± 0.5; M1: 1.5 ± 1.6, p = 0.023 and M2: 3.1 ± 0.8, p = 0.018). Lower rates of meal enjoyment were found at lunch for the morning shifts (M1: 6.4 ± 0.4 and M2: 6.3 ± 0.4) and at dinner for the afternoon shifts (A1: 6.7 ± 0.4 and A2: 6.4 ± 0.4) compared to the other shift days (p<0.05). The main meal of the night shifts, at the workplace, showed lower rates of hunger in the night shifts (N1: 5.1 ± 0.4 and N2: 5.0 ± 0.5) compared to the other days (p<0.05); the first day of the night shift (N1) showed lower energy intake (503 ± 62 kcal) than morning shifts and the second afternoon shift and lower satiety (5.9 ± 0.4) than mornings and afternoon shifts (p<0.005). N1 had a lower appetite for vegetables (2.2 ± 0.9, p<0.05) compared to the morning and afternoon shifts; N1 (4.2 ± 0.9) and N2 (3.7 ± 1.0) had a lower appetite for starchy foods compared to M2 (6.4 ± 0.9, N1: p = 0.026, N2: p = 0.013) and A2 (6.7 ± 0.9, N1:p=0.018, N2:p=0.006); and lower appetite rates for meat on N1 (4.4 ± 1.0) and N2 (3.8 ± 1.0) compared to all other days (p<0.05). Conclusion: There was a higher energy and macronutrient intake during the early hours of the night shifts, which reduces the overnight fasting period and may have implications for metabolic dysregulation. There was an increase in hunger rates, with no decrease in satiety rates as the shift progressed. The variation of hunger, between the main meals of the shifts, tended to lower rates in the night meals, however, these values were not always associated with lower energy intake. In addition, these late-night meals also had a lower appetite for vegetables, meat, and starchy foods. Considering the metabolic impacts of energy distribution at night, in addition to the influence of subjective perceptions on good food choices, understanding the factors that really motivate these workers' food intake needs to be addressed by future studies. This can improve nutritional counseling strategies for shift workers.